1997
DOI: 10.1002/ange.19971091808
|View full text |Cite
|
Sign up to set email alerts
|

Molekular geprägte Polymere als Enzymmodelle mit starker Esteraseaktivität

Abstract: Wie katalytische Antikörper, können molekular geprägte Polymere fungieren, wenn die Hohlräume im Polymer nicht nur die richtige Form haben, sondern auch noch katalytisch wirksame Gruppen enthalten. Es ist jetzt gelungen, für die basenkatalysierte Esterhydrolyse geprägte Polymere herzustellen (siehe Bild), die typische Eigenschaften wie Michaelis‐Menten‐Kinetik, kompetitive Hemmung, Turnover und Selektivität mit guter katalytischer Aktivität verbinden.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
4

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 18 publications
0
22
0
4
Order By: Relevance
“…Several groups have been pursuing this type of approach through molecularly imprinted polymers: Wulff has recently shown that a mixture of amidine-containing monomers (for functional group binding and catalysis), ethylene dimethylacrylate (as a cross-linker) and a phosphonic acid monoester TSA gave, after TSA removal, an imprinted polymer catalyst that accelerates an unactivated ester cleavage around 100-fold and demonstrates Michaelis ± Menten kinetics. [27] Figure 8. A general selection scheme for generating receptors or polymer cavities capable of recognition and catalysis.…”
Section: Discussionmentioning
confidence: 98%
“…Several groups have been pursuing this type of approach through molecularly imprinted polymers: Wulff has recently shown that a mixture of amidine-containing monomers (for functional group binding and catalysis), ethylene dimethylacrylate (as a cross-linker) and a phosphonic acid monoester TSA gave, after TSA removal, an imprinted polymer catalyst that accelerates an unactivated ester cleavage around 100-fold and demonstrates Michaelis ± Menten kinetics. [27] Figure 8. A general selection scheme for generating receptors or polymer cavities capable of recognition and catalysis.…”
Section: Discussionmentioning
confidence: 98%
“…[12,13] These directional interactions are strong enough to provide significant stabilisation in aqueous media and has been used for the buildup of supramolecular structures [13] or in molecular recognition [14] and catalysis. [15] Previously we demonstrated that pentamidine ( Figure 1, n 5) reversibly forms monolayers on carboxylic acid functionalised thiol SAMs on gold. [16] These layers exhibited selectivity for phosphate biomolecules in a subsequent Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, to mimic enzyme behavior, especially esterase activity, numerous experiments have been undertaken by imprinting with transition-state analogues (TSAs). [3,4] Although the earlier attempts to mimic enzyme behavior using imprinted polymers showed only limited catalytic efficiency, significant rate enhancement by catalysis with imprinted polymers has been obtained in recent years. [4] Evidently, increasing the transition-state binding, as well as correctly incorporating and positioning the functional groups is essential for the construction of an effective enzyme model.…”
Section: Jun-qiu Liu and Günter Wulff*mentioning
confidence: 99%